Pendapatan Petani Dusung di Negeri Haruku Kecamatan Pulau Haruku Kabupaten Maluku Tengah - Latuharhary, Wesly F; Kakisina, Leunard O; Luhukay, Johanna M (Jurnal Agrosilvopasture-Tech, 2024)
The purpose of this study is to determine the amount of domestic pet revenue in the Haruku nation. Sampel is conducted in a purposeful manner by calculating the number of tangga houses with uninterrupted power supply based on the total population of 1844 people. The analysis techniques used are both quantitative and qualitative. According to the study's findings, a petani dusung can help meet a household's basic needs by generating an annual revenue of around Rp. 20.751.493.